Internet and its Effects on Memory - Szpunar, Magdalena (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The purpose of this article is to determine the influence of the internet on human memory. The author tries to answer the question of how the extensive use of the Internet can determine the process of remembering. The author treats the dominant medium of the digital age as an external database, which frees us from the process of remembering, because we rely on an external resource, which can be reached at any time. At the same time it is pointed out that the perception of the process of lowering the efficiency and effectiveness of our mind, is not a precedent, because in the past these concerns were articulated about each new medium